(untitled) (American Journal of Business Management, Economics and Banking, 2024)
In the conditions of a developed market economy, various ways of realizing the economic interest of an employee are used, which are reflected in enterprise management models. The most common are the «American» and «Japanese» models, which take into account the peculiarities of the historical and economic development of the two countries and, first of all, the mentality of the population formed over the centuries. In this article highlights of the economic benefit of the employee in developed countries and modern methods of its implementation.